The role of extracorporeal membrane oxygenation in adult liver transplant patients: A qualitative systematic review of literature. Issue 4 (23rd November 2021) - Reid, Trista D.; Kratzke, Ian M.; Dayal, Diana; Raff, Lauren; Serrano, Pablo; Kumar, Aman; Zendel, Alex; Herdman, Victoria; Gallaher, Jared; Carlson, Rebecca; Charles, Anthony G.; Desai, Chirag S.
Abstract: Background: A paucity of evidence exists regarding risks and benefits of extracorporeal membrane oxygenation (ECMO) in adult liver transplantation. Methods: This was a systematic review conducted from January 1, 2000 to April 24, 2020 of adult liver transplant recipients (pre‐ or post‐transplant) and donors who underwent Veno‐arterial or Veno‐venous ECMO cannulation. Death was the primary outcome, with graft function and complications as secondary outcomes. Results: Forty‐one articles were identified that fit criteria. A total of 183 donors were placed on ECMO, with recipient complication profiles and mortality that mirrored rates from standard criteria donors. Sixty‐one recipients were placed on ECMO intraoperatively or postoperatively. Most patients experienced at least one complication with infections as the most common cause and minimal complications specifically related to ECMO use. Multisystem organ failure (MSOF) and infections were more common among liver recipients who died compared to those who survived. Overall mortality at 90 days was 45.9%. Causes of death were most commonly MSOF and infections. Conclusions: ECMO use in adult liver transplantation is a useful adjunct. Recipient morbidity and mortality from donors placed on ECMO parallel that of recipients from standard criteria donors, and morbidity and mortality of recipients placed on ECMO are similar to other ECMO populations. Abstract :